Russian vocabulary third edition - Rakova, Alfia A; parrotta, Ray j (America mc graw hill, 2011)
232 exercises with answers ( the latest terms and expressions that russian speakers use today - english/russian and russian/english glossaries
1
Keywords: Russian languge -- self-instruction; Russian languge